The evolution of civil responsability in contemporary constitutional law: from the moral damage in nature to moral damage in re ipsa - Garatini, Mariana Cristina [UNESP]; Figueira Porto, Ana Luiza [UNESP] (Univ Santiago Compostela, 2017)
Moral damage is a king of indemnity that protects imaterial rights against injuries committed, those rights are inserted within personalities scope, previously deprived of judicial protection, once these rights were used just to protect material goods. On the other hand, currently these subjetives rights are destinated to preserve the most important aspects that makes men unique, the human dignity. With the start of fundamental rights protection in civil order, the injured was required to prove its three indispensable requirements, negligence, malice and causality connection, This obligation, sometimes ended up exposing men to a new humiliating and degrading situation. Then, a new modality was necessary to abadon damages prove, wich is called moral damage in re ipsa and that day by day gains a more relevant space in the legal conjuncture.
Keywords: moral damage; presumed moral damage; civil responsability; negligence; malice; causality connection